Catalytic epoxidation of unsaturated fatty acids in palm stearin via in situ peracetic acids mechanism - Norin Hafizah Rahim; Mohd Jumain Jalil; Nabisab Mujawar Mubarak; Intan Suhada Azmi; Gnanasambandam Anbuchezhiyan (Scientific Reports)
Abstract Epoxidized vegetable oils present a viable substitute for polymers derived from petroleum. This research focuses on the impact of a process parameter on the epoxidation of palm stearin when zeolite ZSM-5 is used as a catalyst. This study synthesized peracetic acid as the oxidizing agent by combining hydrogen peroxide and acetic acid, adjusting molar ratios relative to palm stearin. The optimal relative conversion oxirane (RCO) percentage reached 43.06% at 70 °C, 200 rpm stirring speed, and 0.8 g of catalyst. The acetic acid to palm stearin molar ratio was 1:1, and the hydrogen peroxide to palm stearin ratio was 0.5:1. Both palm stearin and its epoxide derivative have been studied using Fourier-transform infrared spectroscopy, showing the appearance of an oxirane ring at a wavenumber of 1240 cm⁻¹. Kinetic modelling demonstrates that the simulation and experiment show a reasonable discrepancy, considering several assumptions that have been made. After 100 iterations, the reaction rate constant obtained as follows: $$\:{k}_{11}$$ =0.01 mol⋅L−1⋅min−1, $$\:{k}_{12}$$ = 1.85 mol⋅L−1⋅min−1, $$\:{k}_{2}$$ = 29.90 mol⋅L− 1⋅min− 1, and $$\:{k}_{3}$$ = 0.04 mol⋅L−1⋅min−1.